Analysis of Arrhenius activation energy in magnetohydrodynamic Carreau fluid flow through improved theory of heat diffusion and binary chemical reaction. (1st March 2018) - Kumar, R V M S S Kiran; Kumar, G Vinod; Raju, C S K; Shehzad, S A; Varma, S V K
Abstract: In this work, we addressed the characterization of stagnation-point Carreau fluid flow induced due to stretching of chemically reactive surface. The energy expression is incorporated with a new theory of heat diffusion named Cattaneo-Christov, which is an advanced form of Fourier's heat flux formula. The additional term of thermal relaxation time is arisen in Cattaneo-Christov model of heat diffusion. We considered modified Arrhenius energy function with chemical reaction effect. The theory of boundary layer is employed to govern the mathematical phenomenon. The ordinary differential system is obtained by the implementation of suitable similarity variables. The governing system of mathematical expressions is solved by using Runge–Kutta based MATLAB bvp4c package. The derived solutions are sketched for various values of physical constraints on quantities of interest. A comparative study is presented for validating the results. It is found that the larger value of the thermal relaxation parameter act as non-conductor. It also noted that the destructive binary reaction is favorable to enhance the species concentration.